An Analysis of the Influence of Product Quality, Price, and Promotion on Customer Satisfaction of Sambal Nagih Products in Pontianak - Aisyah Yulandari; Muhammad Ebuziyya Alif Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of product quality, price, and promotion on customer satisfaction with Sambal Nagih products in Pontianak City. This research uses an associative quantitative approach with a total of 100 respondents selected using a purposive sampling technique. Data were collected through interviews and questionnaires. The results of multiple linear regression analysis show the equation Y = 1.061 + 0.243X₁ + 0.225X₂ + 0.203X₃, with a correlation coefficient (R) of 0.697, which indicates a strong relationship. The coefficient of determination (R²) value of 48.6% indicates that the variation in customer satisfaction can be explained by product quality, price, and promotion, while the remaining percentage is influenced by other variables outside the model. The F-test results show that product quality, price, and promotion simultaneously have a positive and significant effect on customer satisfaction. The partial t-test results also show that the three independent variables individually have a positive and significant effect. In conclusion, product quality, price, and promotion have been proven to contribute to increasing Sambal Nagih customer satisfaction. This study recommends the need for product innovation improvement, competitive pricing, and more attractive promotions to maintain Sambal Nagih’s competitiveness. Future research is expected to add other variables, such as customer loyalty, to obtain more comprehensive results.